Book review: Mukherji, P. & Albon, D. (2022). Research methods in early childhood: An introductory guide. SAGE Publications. 448 pp. - Paula Martínez Enríquez (Revista Española de Pedagogía, 2025)
Research in the field of early childhood education is a vital and constantly evolving area that requires effective and accessible tools for researchers. The work before us, Research methods in early childhood: An introductory guide, by Penny Mukherji and Deborah Albon, academics linked to London Metropolitan and Roehampton universities respectively, contributes to this specific need. This work has a structured and methodological focus that guides readers in the process of research in early childhood education, from conceptualisation to data analysis. Accordingly, the work’s introduction lays a solid foundation by defining concepts such as basic, applied, evaluation, action, and targeted research.